?HYDROCHLORIC ACID LEACHING OF SPHALERITE IN THE PRESENCE OF AN OXIDIZING AGENT (Biological Sciences - PJSIR, 1999)
Dissolution experiments of a natural sphalerite ore from Nigeria were carried out in hydrochloric acid -potassium chlorate (v) solutions at various temperatures to study the physico-chemical factors and the mechanism for the leaching of zinc from this mineral. The dissolution rate was strongly influenced by the temperature and concentration of the leaching reagent. It was, however, independent of the stirring speed over the range 0 -400 rpm and fitted the kinetic equation based on the shrinking core model for chemical reaction control. An activation energy of about 43 kJ mol' was calculated for the leaching process.